Implementasi Sistem E-learning Untuk Program Kejar Paket B dan C Pada PKBM (PUSAT KEGIATAN BELAJAR MASYARAKAT) Woyo - Azmi, Khairul; Ahmad Asyahri (Jurnal Teknologi Komputer dan Informasi, 2024)
The implementation of an e-learning system for the Kejar Paket B and C programs at PKBM (Community Learning Activity Center) Woyo aims to enhance the quality of learning and educational accessibility for students. This system is designed with various features such as online learning modules, discussion forums, online exams, and progress monitoring. By implementing e-learning, it is expected to increase student participation and motivation, providing flexibility in the learning process. This system also facilitates interaction between teachers and students, creating a more interactive and effective learning environment. This implementation is anticipated to serve as a model for other PKBMs in improving the quality of non-formal education in Indonesia.